2009
DOI: 10.1111/j.1365-3024.2009.01132.x
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant effect of LPS and killedPropionibacterium acneson the development of experimental gastrointestinal nematode infestation in sheep

Abstract: Gastrointestinal helminthic infection is an important worldwide sheep disease. The emergence of anthelminthic resistance has led to drives to seek new means of therapeutic control of helminthiasis in sheep. Several data demonstrated the adjuvant effect of Propionibacterium acnes on resistance to infection. Herein, we evaluate the adjuvant effect of the commercial suspension containing LPS and P. acnes on experimental helminthiasis. Sheep received three doses of LPS and P. acnes commercial suspension or saline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 51 publications
1
7
0
Order By: Relevance
“…Various approaches have been developed recently in order to improve vaccine potency, particularly with the respect to choose of a better adjuvant. To date, despite various adjuvants, such as lipopolysaccharide (LPS) and Freund's complete adjuvant (FCA), have been identified and extensively studied, they are not widely applied due to their toxicity (Abel et al, 2009;Pohanka, Vobornikova, & Fusek, 2016). Hence, only partial adjuvants, such as alum, are licensed for clinical use (Mbow, Gregorio, Valiante, & Rappuoli, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Various approaches have been developed recently in order to improve vaccine potency, particularly with the respect to choose of a better adjuvant. To date, despite various adjuvants, such as lipopolysaccharide (LPS) and Freund's complete adjuvant (FCA), have been identified and extensively studied, they are not widely applied due to their toxicity (Abel et al, 2009;Pohanka, Vobornikova, & Fusek, 2016). Hence, only partial adjuvants, such as alum, are licensed for clinical use (Mbow, Gregorio, Valiante, & Rappuoli, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Present experiment achieved lower protection levels than those obtained, with the same recombinant, using aluminum adjuvant [7, 8]. Lack of statistical significance of differences between lambs vaccinated and those treated only with the BI (Group 1 versus group 2) does not allow to exclude the possibility of BI eliciting some unspecific protection as shown in adult animals [15] despite the lower values found in rHc23-vaccinated animals. Whether or not the lower efficacy obtained is due to the infection schedule, the immunization system (adjuvant versus immunostimulant, timing) or to the size of experimental groups should be studied.…”
Section: Discussionmentioning
confidence: 59%
“…At the end of last century, the commercialization agents based on P. acnes began to be used for animal immune regulation (Flaminio, Rush et al 1998). In general, P. acnes played a role in non-specific immune protection by the study of immune stimulation, such as parasites (Iseki, Takabatake et al 2008;Abel, Chen et al 2009) or viruses (Megid and Kaneno 2000). Our study for the first time showed that P. acnes for specific heterologous protective immunity could develop into a possible A. pleuropneumonia vaccine or adjuvant.…”
Section: Discussionmentioning
confidence: 76%
“…P.acnes is one kind of microorganism usually seen in nature, which is related to the inflammation in acne in human skins (Thiboutot 2008). P.acnes could enhance the resistance of animals to a variety of pathogens such as parasites (Clark, Cox et al 1977;Abel, Chen et al 2009), bacteria (Miyata, Nomoto et al 1980;Dinsmore, Cattell et al 1995) and viruses (Kirchner, Hirt et al 1977;Megid, Cremonini et al 2002), by improving the non-specific immunity of animals. In our previous work, we found that several potential vaccine candidate genes of A.pleuropneumoniae showed remarkable simiariities to those of the genes serotypes of P.acnes (Lei, Sun et al 2008).…”
Section: Introductionmentioning
confidence: 99%